Law Enforcement Issues and Regulations in Undelimited Maritime Boundaries: An International Law Perspective - Esther Christie Erlina; Raden Ahmad Gusman Catur Siswandi (University of Jember, 2020)
Maritime boundaries play an essential role in determining the state's sovereignty, rights to exploit natural resources, maintain security, and territorial integrity. However, maritime boundaries often overlap between states, which can amount to conflicts. Maritime areas whose boundaries have not been agreed between neighboring states are referred to as “undelimited maritime boundaries” (UMB). Indeed, Article 74 of the United Nations Convention on the Law of the Sea 1982 has set out rules regarding UMB. However, conflicts still arise between states; for instance, the conflict related to law enforcement between Indonesia and Viet Nam in the South China Sea. This study aims to analyze law enforcement issues and the rights and obligations of states in UMB under international law. This study uses normative legal research which applies the method of legislative, conceptual, and analytical approaches. This study finds that states involved in UMB are prohibited from carrying out excessive law enforcement since it could trigger more conflicts and will hamper the ongoing final maritime delimitation negotiation process. In order to ensure zero conflicts during the negotiation process, this paper recommends that Indonesia should make every effort to enter into a comprehensive provisional arrangement about UMB with its neighboring states. Keywords: International Law, Law Enforcement, Undelimited Maritime Boundaries.